Correlation Between Apical, Anterior, and Posterior Vaginal Wall Prolapse with Voiding Dysfunction: A Single Center Retrospective Cohort Study - Zinat Ghanbari; Fatemeh Asadi; Shahrzad Amirlatifi; Mamak Shariat; Tahereh Eftekhar; Maryam Deldar; Razieh Vahdani (Tehran University of Medical Sciences, 2024)
Objective: Voiding Dysfunction (VD) is one of the most common disorders among women, which is characterized by a disorder in urination. Pelvic organ prolapse is one of the factors that can affect VD. In this study, the relationship between prolapse in the anterior, posterior, and apical areas and VD has been evaluated. Materials and methods: This is a cohort retrospective study. The participants in this study were women with VD, who referred to the pelvic floor disorders clinic of Imam Khomeini Hospital in Tehran in 2018-2020. Clinical information was obtained retrospectively from the hospital's electronic data system, also symptoms (intermittent stream, incomplete voiding, poor flow, post void dribble, straining to void, stage anterior, posterior and apical) and urodynamic parameters (including EMG, PVR100, Qmax12, and pdet20) were evaluated, which included detailed questionnaires (Urinary Distress Inventory 6 (UDI-6) and Incontinence Impact Questionnaire-7 (IIQ-7)), pelvic examination, and complete urodynamic evaluation. Results: There was a direct relationship between the age of the patients and the stage of prolapse (p<0.001). So that, the stage increased with age. In addition, it was found that the severity of urinary symptoms is related to the stage of prolapse in the apical area (p=0.001). Also, the results showed that intermittent stream symptoms and the symptoms of staining to void had a significant relationship with the stage of prolapse (III and IV) in the apical and anterior areas. Also, it was shown that only PVR > 100 had a significant relationship with the stage of prolapse in the apical area (p=0.001). Conclusion: Intermittent stream and straining to void were related to the stages of prolapse in the apical and anterior regions. It was also concluded that the greater the prolapse, the higher the value of PVR > 100.